The effect of chewing gum on oral mucositis in children receiving chemotherapy - (:unkn) unknown (Technological Educational Institute of Athens, 2014)
Background: Oral mucositis is an important clinical problem, resulting in significant patient morbidity, a change in health-related quality of life, and supportive care. The purpose of this study was to assess the efficiency of chewing gum on children, who are receiving chemotherapy regimens, for prevention and treatment of oral mucositis. Method and Material: The study sample consisted of 60 children (30 study group-30 control group) between the ages 6-18 years. All the children have received chemotherapy at least once. Study group children chewed non-sugar gums three times a day at least 20 minutes during 10 days. In oral assessment, WHO Oral Mucositis Assessment Scale and Eilers' Oral assessment Guide was used and also salivary pH measurement was done. Results: The rate of children who was assessed as Grade 1 and Grade 2, decreased 46.1% in study group and this rate decreased to 20.8% in the control group. At the beginning of the study, 13.3% of the study group children were assessed as Grade 3 but at the end of the study none of the children were observed at Grade 3. Also, statistically significant difference was found between study and control groups' pH values. Conclusion: The results of that study show new evidence about preventing and decreasing severity of oral mucositis for the children, receiving chemotherapy.
Keywords: Chewing gum; Children; Nurse; Oral mucositis